Weeding the reference collection : updating and upgrading of the University of Malaya reference collection at the Main Library - Sinnasamy, J. (University of Malaya Library, 2010)
The reference collection at the University of Malaya Library was reviewed intensely for the first time since its inception. It was a major task to review the entire print reference collection which amounted to over 7,000 titles. About RM300,000.00 was allocated for this purpose and a taskforce was setup to update and upgrade the reference collection during the semester break of the 2008/2009 academic session. The collection now consists of materials published in year 2000 and above. However, books of high value despite the age have been retained. The updated reference collection has been relocated to another floor to give it a new appealing image. The planning, implementation and the criteria used in this project are described.